Ascorbate as a Co-Factor for Fe- and 2-Oxoglutarate Dependent Dioxygenases: Physiological Activity in Tumor Growth and Progression - Kuiper, Caroline; Vissers, Margreet C. M. (Frontiers in Oncology, 2014)
Ascorbate is a specific cofactor for a large family of enzymes known as the Fe- and 2-oxoglutarate-dependent dioxygenases. These enzymes are found throughout biology and catalyse the addition of a hydroxyl group to various substrates. The proline hydroxylase that is involved in collagen maturation is well known, but in recent times many new enzymes and functions have been uncovered, including those involved in epigenetic control and hypoxia-inducible factor (HIF) regulation. These discoveries have provided crucial mechanistic insights into how ascorbate may affect tumour biology. In particular, there is growing evidence that HIF-1-dependent tumour progression may be inhibited by increasing tumour ascorbate levels. However, rigorous clinical intervention studies are lacking. This review will explore the physiological role of ascorbate as an enzyme cofactor and how this mechanism relates to cancer biology and treatment. The use of ascorbate in cancer should be informed by clinical studies based on such mechanistic hypotheses.